Hubungan Persepsi Siswa tentang Pola Asuh Orang Tua dengan Kesadaran Beragama Siswa Sekolah Menengah Pertama 2 Pekanbaru - Rozi, Pahrul; Yeli, Salmaini; Anwar, Khairil (YASIN, 2024)
Religious awareness is very important for students to have in shaping their character so that they can instill noble morals and become people who have strong faith and devotion. This study aimed to analyze the correlation between students' perceptions of parenting patterns and religious awareness of students at Muhammadiyah 2 Junior High School, Pekanbaru. This study used a quantitative correlational approach. The population was all students of Muhammadiyah 2 Junior High School, Pekanbaru, totaling 168 students with a sample size of 118 students. The sampling technique used was simple random sampling. The data collection technique employed was a questionnaire. The data analysis techniques used were questionnaire instrument prerequisite tests (validity and reliability tests), multiple correlation requirement tests (normality and linearity tests), and research hypothesis tests (bivariate & multivariate correlation tests). Research results: It was found a significant positive correlation between the relationship between students' perceptions of parenting patterns and religious awareness of students at Muhammadiyah 2 Junior High School Pekanbaru as evidenced by the sig. 0,000 < 0,050 H0 accepted Ha rejected, by the value of R = 0.735 at a strong level between.